ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA PT BFI FINANCE TBK DAN PT ADIRA DINAMIKA MULTI FINANCE TBK BERDASARKAN RASIO SOLVABILITAS, AKTIVITAS, DAN PROFITABILITAS TAHUN 2023–2024 - Burhamzah, Rahmat; Dg Macenning, A. Reski Almaida (Gapenas Publisher, 2025)
This research aims to analyze and compare the financial performance of PT BFI Finance Tbk and PT Adira Dinamika Multi Finance Tbk in the period 2023–2024 using solvency, activity, and profitability ratios. The study adopts a quantitative descriptive comparative approach based on secondary data derived from audited annual financial reports. The analysis focuses on indicators such as Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), Total Asset Turnover (TATO), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The results show that PT BFI Finance Tbk demonstrates stronger financial stability and better operational efficiency than PT Adira Dinamika Multi Finance Tbk, particularly in managing capital structure and maintaining profitability margins. Conversely, PT Adira Finance exhibits a decreasing trend in asset utilization efficiency and profit margins. These findings indicate the importance of maintaining balanced capital structures and operational effectiveness to enhance long-term financial health. The study provides valuable insights for investors, management, and stakeholders in evaluating the performance and competitiveness of financial service institutions in Indonesia’s non-bank financing industry.